Optimization of sulfonation process for the development of carbon-based catalyst from crambe meal via response surface methodology. (1st August 2020) - Fonseca, Jhessica M.; Spessato, Lucas; Cazetta, André L.; Bedin, Karen C.; Melo, Sandra A.R.; Souza, Flavio L.; Almeida, Vitor C.
Graphical abstract: Highlights: Crambe meal was used as precursor of sulfonated carbon. Sulfonation process was optimized from response surface methodology. Sulfonated carbon showed acid density of 2.19 mmol g −1 . Sulfonated carbon was applied as catalyst in esterification reaction of oleic acid. Abstract: In this work, crambe meal was successfully used as precursor of sulfonated carbon-based catalyst for reaction of esterification of the oleic acid. The effects of the variables, temperature, time and H2 SO4 :carbon ratio of the sulfonation process on the acid density were investigated and optimized, using the Central Composite Rotatable (CCR) design and Response Surface Methodology (RSM). The results showed temperature and H2 SO4 :carbon ratio have a great influence on the acid density of the catalyst. The optimum condition of sulfonation process was found to be: temperature of 122 °C, time of 85 min and H2 SO4 :carbon ratio ( v:w ) of 3:1, which provided an optimized sulfonated carbon (SCop ) with density acid of 2.19 mmol g −1 . The characterization of materials presented significant changes in the chemistry composition and morphologic features of SCop when compared to raw material. The SCop showed features of amorphous material, with sulfonic groups (-SO3 H) on the surface, which gave it acidic characteristics. Additionally, the SCop showed thermal stability up to 300 °C, and good catalytic activity for the esterification reaction of the oleic acid.